Revitalising heritage shophouses of Kota Bharu Kelantan / Yasmin Mohd Faudzi ... [et al.] - Mohd Faudzi, Yasmin; Md Alwi, Najah; Anuar, Nor Hafizah; Mohamad, Juliza; Hanafi, Nik Nurul Hana (2021)
This project highlights how the exterior facade of a heritage shophouse building, including their associated signage and advertising, as a crucial element in retaining and safeguarding the features of local and traditional cityscape. The focused concern is on maintaining the very few last remaining historical pieces of architecture in the old city of Kota Bharu by finding ways to fit them back into the changing urban environment they are located in. Armed with city heritage guidelines provided by the local authorities of MPKB, twenty new design proposals of two rows of shophouses in Jalan Temenggung were presented as an alternative to the current existing sites by the second-year architecture students. The results showed a highly viable solution that would bring gains to many different stakeholders. Undoubtedly, the process for enforcement, application and continued maintenance of these heritage buildings will constantly be competing with factors such as private ownership, finances, and relevance of placement in its surroundings. This study reveals, however, how the intrinsic value of these historical pieces is more likely to go up when investments are made to communicate their worth.